Pengaruh Edukasi melalui Media Audio Visual terhadap Pengetahuan dan Sikap Remaja Overweight - Meidiana, Risma; Simbolon, Demsa; Wahyudi, Anang (Politeknik Kesehatan Tanjungkarang, 2018)
One of the nutritional problems that occur is overweight. The level of knowledge nutrition in an adolescent is one of the factors that can affect the occurrence of obesity in adolescents. Most occurrences of nutritional problems are more or less avoidable if adolescents have sufficient knowledge and attitudes about maintaining nutrition and managing food. This research was a quasi-experimental study with a pre-post test with control group design. The subjects of this study were overweight adolescents totaling 40 people, the intervention group received education through audiovisual media while the control group with leaflets. The results showed the average value of knowledge and attitudes of adolescents after and before being given education for Leaflet groups were the average value of knowledge before 8.60 and after 9.48, attitudes value before 36.58 and after 40.38. While audiovisual media groups, the average value of knowledge before 8.83 and after 9.42, values for attitudes before 36.45 and after 39.65. There was an influence of education by using audiovisual media and leaflets to increase the knowledge and attitudes of overweight adolescents. Suggestions for schools to be able to use audiovisual media and leaflets as a medium to educate nutrition about students in schools so that they can apply daily life and remind each other to lose weight and live healthy lives.